A localização dos pobres nas cidades brasileiras : um estudo sobre a situação dos assentamentos humanos às margens da lagoa Mundaú em Maceió, Alagoas. - Melo, Taina Silva (2010)
The current work has as its general theme the solutions-locations found by the poorest part of the population of Brazilian cities in terms of housing. It specifically addresses the appropriation of environmentally sensitive areas in urban locations for that purpose, (more precisely, the edges of urban water bodies), and the conflicts (social, environmental and, consequently, political) that surround such situations. The research is a case study which has as its empirical focus the situation of the human settlements on the banks of the Mundaú Lagoon in Maceió, capital of Alagoas, and takes as its starting point the hypothesis that "the urban environmental issue is primarily a housing problem and a problem of the adoption of policies that will facilitate the access of the majority of the population to adequate housing". (Martins 2002, p.126) The discussion focuses initially on the relationship between the process of urbanization and poverty in Brazil, contextualizing the settlements of the poorest part of the population of Brazilian cities and specifically of the city of Maceió. This is followed by a discussion of the socio-environmental dimension of human settlements in environmentally sensitive areas, especially those located on the shores of Mundaú Lagoon. Later, we discuss public policies for the promotion of housing for the poorest in Brazilian cities, with emphasis on those policies which are related to the human settlements on the banks of Mundaú Lagoon, and point out the conflicts of interest that permeate the decisions of public authorities, especially those with respect to the use and occupation of environmentally fragile areas in the urban space. The work leads us to understand that the phenomenon of precarious human settlements in environmentally fragile areas is the result of the reproductive processes of the socio-spatial inequalities inherent in the reproduction of urban space in Brazil. In this manner we come to see the urban environmental issue as a problem that stems from the difficulties of access to adequate housing of most of the population. While this access is determined by the income of the population the place of the poor will be a place ever more excluded from the benefits of the city.